1998
DOI: 10.1148/radiology.209.3.9844655
|View full text |Cite
|
Sign up to set email alerts
|

Stage III multiple myeloma: clinical and prognostic value of spinal bone marrow MR imaging.

Abstract: MR imaging patterns of spinal bone marrow involvement are correlated with several clinical parameters of disease severity and have prognostic value in stage III multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 0 publications
2
65
0
1
Order By: Relevance
“…In these patients, wb-MRI is a more sensitive technique [6,30], which has been confirmed by the present study where diffuse infiltration was not visualized in 75% and focal-diffuse infiltration in 84% of the patients on Xray survey. In line with other studies in the literature, the examinations were performed with T2-weighted STIR sequences, as first described by Rahmouni et al [31], and with T1-weighted sequences [9], which have a high [33] who reported false-negative results in 26% of the biopsy specimens. In some studies, it could be shown that a diffuse pattern of infiltration as seen on the skeletal survey correlates significantly with the histologic findings.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In these patients, wb-MRI is a more sensitive technique [6,30], which has been confirmed by the present study where diffuse infiltration was not visualized in 75% and focal-diffuse infiltration in 84% of the patients on Xray survey. In line with other studies in the literature, the examinations were performed with T2-weighted STIR sequences, as first described by Rahmouni et al [31], and with T1-weighted sequences [9], which have a high [33] who reported false-negative results in 26% of the biopsy specimens. In some studies, it could be shown that a diffuse pattern of infiltration as seen on the skeletal survey correlates significantly with the histologic findings.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, MRI is playing an increasing role in the diagnosis of multiple myeloma [8]. Various authors have demonstrated the high sensitivity of MRI in detecting plasma cell infiltrations [2,6,7,[9][10][11][12]. In contrast to conventional skeletal X-ray surveys (X-ray survey), MRI can precisely evaluate the bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…Independent studies by Moulopoulos et al [6] and Vande Berg et al [7] suggested that patients with stage I disease who had normal-appearing bone marrow on MRI had a longer progression-free interval, and patients with bone marrow involvement evident on MRI had more rapid progression of the disease. In a study of 80 patients with stage III multiple myeloma, Lecouvet et al [8] showed that a good or partial response to chemotherapy (determined by a 50-75% decrease in serum or urine myeloma protein) was more common in patients with normal-appearing marrow on MRI than in patients with an abnormal-appearing marrow (89% versus 68%, respectively). A diffusely abnormal pattern of bone marrow also correlated with more marked alterations in other clinical parameters of disease activity such as serum calcium, t32 microglobulin and hemoglobin levels, indicating more severe disease than found in patients with a focally abnormal MRI pattern of bone marrow [8].…”
Section: Lymphoproliferative Diseasesmentioning
confidence: 99%
“…In a study of 80 patients with stage III multiple myeloma, Lecouvet et al [8] showed that a good or partial response to chemotherapy (determined by a 50-75% decrease in serum or urine myeloma protein) was more common in patients with normal-appearing marrow on MRI than in patients with an abnormal-appearing marrow (89% versus 68%, respectively). A diffusely abnormal pattern of bone marrow also correlated with more marked alterations in other clinical parameters of disease activity such as serum calcium, t32 microglobulin and hemoglobin levels, indicating more severe disease than found in patients with a focally abnormal MRI pattern of bone marrow [8]. Stabler et al [1] evaluated five types of infiltration patterns and confirmed the prognostic value of MRI in staging of, and in planning treatment for, multiple myeloma.…”
Section: Lymphoproliferative Diseasesmentioning
confidence: 99%
“…In patients with monoclonal plasma cell disease, FLs and diffuse infiltration detected by MRI are significant prognostic markers for progression free and overall survival. [8][9][10][11] Until now, it has not been clear whether the assessment of remission can be matched with changes in MRI. Also, it has not yet been clarified whether residual changes in bone marrow such as FLs may be the source of disease relapse.…”
Section: Introductionmentioning
confidence: 99%